COMPUTER SUPPORTED EDUCATION - RESULTS OF RESEARCH PROBE - DOSTAL, Jiri; Milan, KLEMENT (Trends in education, 2012)
This paper presents results of the research realized on the schools in the Czech Republic. It focuses on the findings of fact, how often teachers use a computer and the internet. It was found that teachers use a computer and the internet to prepare to instruction, to communicate with pupils and parents, to further self-education and directly in instruction.
Keywords: computer based instruction; e-learning; ICT; research; education.